Hunt us the fox: False poem for Julián Ríos - Cerviño, Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Hunt us the fox (poem)
Keywords: Julián Ríos; Poetry; Ángel Cerviño; Tribute